RETRACTED: Xianglian Pill Suppresses Inflammation and Protects Intestinal Epithelial Barrier by Promoting Autophagy in DSS Induced Ulcerative Colitis Mice - Wang, Bingyu; Gong, Zhiqiang; Zhan, Jingyu; Yang, Lei; Zhou, Quanyu; Yuan, Xingxing (Frontiers in Pharmacology, 2021)
Xianglian pill (XLP) is a typical traditional Chinese herbal medicine prescription composed of Coptidis Rhizoma and Aucklandiae Radix. It has been used to treat gastrointestinal disease for centuries. In the present study, the potential mechanisms of XLP in the treatment of ulcerative colitis (UC) were predicted by integrative pharmacology-based approach. Then, the main compounds of XLP were detected by liquid chromatography-mass spectrometry (LC-MS/MS). Finally, we verified the mechanism of XLP in the treatment of UC in a dextran sulfate sodium (DSS) model. C57BL/6 mice were randomly divided into the control group, DSS group, 5-aminosalicylic acid (5-ASA) group which was used as the positive drug control, XLP low, medium, and high dose group, with 10 mice per group. Except for the control group, acute colitis model was induced in the other mice by administering 3% DSS for consecutive 7 days. Mice in 5-ASA and XLP groups were administered with 5-ASA (50 mg/kg) or XLP (0.8, 1.6, 3.2 g/kg) via oral gavage once per day respectively. Body wight and disease activity index were assay during drug intervention. On day 8, all animals in this experiment were sacrificed and colon tissues were collected for analysis after measurement of the length. The results showed that XLP alleviate DSS -induced acute colitis in mice, including inhibition the secretion of pro-inflammatory cytokines, repairing the dysfunction of intestinal epithelial barrier, enhanced autophagy, and blocked the activation of PI3K/Akt/mTOR pathway. Furthermore, inhibiting autophagy by 3-methyladenine attenuated the protective effects of XLP on colitis. The underlying mechanism may be that Xianglian pill promote autophagy by blocking the activation of PI3K/Akt/mTOR signaling pathway.